Unexpectedly High Beta-Diversity of Root-Associated Fungal Communities in the Bolivian Andes - Barnes, Christopher J.; Maldonado, Carla; Frøslev, Tobias G.; Antonelli, Alexandre; Rønsted, Nina (Frontiers in Microbiology, 2016)
Bolivia is one of the most biologically diverse countries on the planet. Between the Andes and the Amazon drainage basin spans the Yungas, a vast forested region shown to be extremely species rich in macro-organisms. However, it remains unclear whether this high diversity is also reflected in microbial diversity. Here we assess the genetic, taxonomic and functional diversity of root-associated fungi surrounding Cinchona calisaya calisaya trees, a typical element of the intermediate altitudes of the Bolivian Yungas. We determine the relative effects of edaphic properties, climate, and geography in regulating fungal community assembly. We show that α-diversity for these fungal communities was similar to temperate and arid ecosystems, averaging 90.1 operational taxonomic units (OTUs) per sample, with reads predominantly assigned to the Ascomycota phylum and with a saprotrophic lifestyle. ß-diversity was calculated as the distance-decay rate, and in contrast to α-diversity, was exceptionally high with a rate of -0.407. Soil properties (pH and P) principally regulated fungal community assembly in an analogous manner to temperate environments, with pH and phosphorus explaining 7.8 % and 7.2 % of community variation respectively. Surprisingly, altitude does not influence community formation, and there is limited evidence that climate (precipitation and temperature) play a role. Our results suggest that sampling should be performed over a wide geographical and environmental range in order to capture the full root-associated fungal diversity in subtropical regions. This study sheds further light on the diversity and distribution of the world's "hidden biodiversity".